The use of Haas appliances in the treatment of orthodontic problems (Research, Society and Development, 2022)
Given the complexity of orthodontics and more specifically of the posterior crossbite that can be associated with maxillary or mandibular deficiency and even with the presence of a skeletal class III, this study aimed to evaluate changes in the transverse dimension of the upper dental arch in patients with Complete unilateral cleft lip and palate who underwent rapid maxillary expansion and compare the results with Haas or Hayrax device. Thus, the mechanism of action of the Hass device was presented and the positive (or negative) clinical effects of the Haas device were discussed. In the methodology, the present research was based on a study of systematic literature review, of a qualitative and exploratory nature, with a theoretical approach based on periodical databases, PubMed, Google Scholar and Scielo, whose time frame was between the years 2017 to 2022. In the results, it was clear to see that the Haas breaker device is an efficient device for achieving transverse maxillary growth.